2018
DOI: 10.2991/j.jegh.2018.08.103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Health Education on Menopause Symptoms and Knowledge and Attitude in Terms of Menopause

Abstract: This study was carried out to evaluate the effectiveness of health education on menopausal symptoms, knowledge, and attitudes about menopause. To evaluate the efficacy of a training program, information about menopausal symptoms, knowledge, and attitude toward menopause was collected before and after health education. After the health education intervention, it was determined that there was a decrease in the somatic and psychological subdimensions of the menopausal symptom evaluation scale and in the total sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 19 publications
5
29
0
3
Order By: Relevance
“…Data from Brazilian women, aged 45–60 years, confirmed that higher education level was significantly associated with a higher knowledge on menopause [ 12 ]. A study of 44 Turkish women (with a mean age of 50.41 ± 6.36 years) living in the district centre of Beylikova and having mostly a lower educational level showed positive changes in menopause-related level of knowledge after a planned training programme [ 13 ]. Similar results were seen in Eritrean women, where the structured educational intervention was beneficial to the women in improving their knowledge of and attitude toward menopause [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from Brazilian women, aged 45–60 years, confirmed that higher education level was significantly associated with a higher knowledge on menopause [ 12 ]. A study of 44 Turkish women (with a mean age of 50.41 ± 6.36 years) living in the district centre of Beylikova and having mostly a lower educational level showed positive changes in menopause-related level of knowledge after a planned training programme [ 13 ]. Similar results were seen in Eritrean women, where the structured educational intervention was beneficial to the women in improving their knowledge of and attitude toward menopause [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing level of education, women accept menopause as a natural developmental occurrence in life, like childhood and puberty [44]. Education increases women's self-consciousness and informs them about the bodily changes and menopausal symptoms [45], thereby improving their attitude toward menopause. Furthermore, like prior studies among seronegative women, older age has been reported as a factor in a positive attitude toward menopause in the current study, too.…”
Section: Discussionmentioning
confidence: 99%
“…Dengan adanya kelompok pendamping, para ibu dapat berbicara bertukar informasi dan saling menguatkan satu sama lain. (Shariat Moghani, 2018) Pendidikan kesehatan merupakan metode yang efektif mengubah tingkat keparahan gejala menopause yang dirasakan dan tingkat pengetahuan dan sikap ibu terkait menopause (Koyuncu, Unsal, & Arslantas, 2018). Pendekatan holistik dengan pemberian edukasi dan support system sebagai salah satu intervensi untuk ibu menopause sangat berpengaruh positif, hal ini ditandai dengan peningkatan kesehatan ibu menopause baik fisik maupun psikologis.…”
Section: Hasil Dan Pembahasanunclassified